Why talk about gender and rice in Latin America? - Koningstein, Manon; Gumucio, Tatiana; Martínez, Jose Maria (2016)
Usually we don't think it's important to talk about gender and rice in Latin America, but three socio economic studies on rice in Ecuador, Peru and Bolivia show that women do contribute to rice production. A whiteboard animation summarizing the research by CIAT and GRiSP.